長期休薬の後に発症したプロピルチオウラシル誘発性ANCA関連血管炎の一例 - 孫, 瑛洙; 伊藤, 量基; 和田, 孝彦; 木畑, 佳代子; 嶋元, 佳子; 真鍋, 和代; 安室, 秀樹; 田中, 晶大; 澤井, 宏和; 尾崎, 吉郎; 福原, 資郎 (臨床リウマチ, 2010)
Here, we report a case of myeloperoxidase-anti-neutrophil cytoplasmic antibody (MPOANCA)-related vasculitis. The patient had been treated with propylthiouracil for Basedow’s disease. Propylthiouracil administration was ceased 20 years ago following thyroid surgery. A 46-year-old woman with a 26-year history of Basedow’s disease and 12-year history of rheumatoid arthritis was admitted with high fever and pulmonary hemorrhage. Results of laboratory evaluation were: CRP 7.54 mg/dL, Cr 4.54 mg/dL, Hb 6.8 g/dL. A diagnosis of MPO-ANCA-associated vasculitis was strongly suggested by positivity for MPO-ANCA (352EU), pulmonary hemorrhage, acute nephritis, and scattered purpura on the limbs. However patient condition did not allow histological confirmation of the diagnosis. She was treated with methylprednisolone pulse therapy and prednisolone. Consolidation on chest X-ray and C-reactive protein levels improved rapidly. However, pulmonary hemorrhage was repeated four times with tapering of prednisolone. The titer of MPO-ANCA showed a linear decrease during the clinical course. The recurrence of pulmonary hemorrhage was correlated with the level of CRP. MPO-ANCA-associated vasculitis was caused by propylthiouracil. It was reported that serum ANCA may still remain positive in the majority of patients with propylthiouracil-induced MPO-ANCA positive for up to 5 years. This patient developed MPO-ANCA-associated vasculitis from taking propylthiouracil 20 years previously. ANCA was detected in more than 20% of patients treated with propylthiouracil, but only 6.5% of patients showed clinical evidence of vasculitis. Long-term follow-up may be necessary after discontinuation of propylthiouracil. Basedow氏病に対して甲状腺亜全摘を受けるまでの間プロピルチオウラシル（PTU）内服治療を受け，20年前に内服終了となった46歳の女性が，喀血を主訴に紹介された．気管から泡沫状血清分泌物が吸引され，MPO-ANCA 352EUなどからANCA関連血管炎に起因する肺胞出血と診断．mPSLパルス療法などで加療した．本症例は内服終了長期を経て発症したPTUに起因するANCA関連血管炎と考えられた．